2019
DOI: 10.3390/cancers11121915
|View full text |Cite
|
Sign up to set email alerts
|

Retinoic Acid Receptors in Acute Myeloid Leukemia Therapy

Abstract: Retinoic acid (RA) signaling pathways regulate fundamental biological processes, such as cell proliferation, development, differentiation, and apoptosis. Retinoid receptors (RARs and RXRs) are ligand-dependent transcription factors. All-trans retinoic acid (ATRA) is the principal endogenous ligand for the retinoic acid receptor alpha (RARA) and is produced by the enzymatic oxidation of dietary vitamin A, whose deficiency is associated with several pathological conditions. Differentiation therapy using ATRA rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(50 citation statements)
references
References 113 publications
0
44
0
Order By: Relevance
“…All-trans retinoic acid (ATRA), the active metabolite of vitamin A, is used in the treatment of acute promyelocytic leukemia, with remarkable results [1,2]. ATRA is a non-conventional anti-tumor drug, being the first example of a cyto-differentiating agent [3].…”
Section: Introductionmentioning
confidence: 99%
“…All-trans retinoic acid (ATRA), the active metabolite of vitamin A, is used in the treatment of acute promyelocytic leukemia, with remarkable results [1,2]. ATRA is a non-conventional anti-tumor drug, being the first example of a cyto-differentiating agent [3].…”
Section: Introductionmentioning
confidence: 99%
“…Peretinoin was found to activate transcription through retinoic acid receptor (RAR) and retinoid X receptor (RXR), and could activate the differentiation of human acute promyelocytic leukemia in HL-60 cells [ 22 , 23 ]. Peretinoin significantly inhibited hepatocarcinogenesis in rat chemical carcinogenesis models using 3′-methyl-4-(dimethylamino)azobenzene (3′-MeDAB) and diethylnitrosamine (DEN) [ 24 , 25 ], suggesting that peretinoin was also involved in suppressing hepatocarcinogenesis.…”
Section: Peretinoinmentioning
confidence: 99%
“…Retinoic acid, a bioactive metabolite of vitamin A, is involved in regulating a large number of biological processes including cellular proliferation, differentiation and apoptosis. RARs (RARα, RARβ and RARγ), and RXRs are the retinoid receptors [71,72]. Studies have shown that the aberrant expression of RARγ is associated with the development of cancers including hepatocellular carcinoma [73].…”
Section: Retinoic Acid Receptorsmentioning
confidence: 99%